Expanding the boundaries: investigating the integration of contextual information across a spectrum of inter-trial variability - Qiu, Ruyi; Mo, Yanzhi (Frontiers in Psychology, 2024)
It is well-documented that feature integration across perception and action creates a retrievable episodic representation, known as a stimulus-response episode or an event file. Previous studies have demonstrated that a task-irrelevant stimulus, which functions as contextual information, can be integrated in various ways. In some cases, the context modulated the binding between a stimulus and a response, resulting in a configural binding structure. In other cases, the context was found to be directly bound with the response in a binary fashion. The current study examined the integration of context within a stimulus-response (S-R) episode, with a focus on the role of inter-trial variability. Specifically, the context variability was manipulated across five experimental groups, ranging from the minimum to the maximum level. The minimum-variability group maintained a consistent pattern of two context tones per block, while the maximum-variability group used a uniformly random order of eight different context tones.Intermediate groups progressively employed greater degrees of variability in the presentation of contextual stimuli. Results showed that the integration of context changed as a function of its variability level: The contextual stimuli with minimal to low level of variability did not exhibit a pattern of integration, while those with moderate to high variability were involved in a configural binding with another stimulus and the response. Only when the context exhibited maximal variability did it become directly bound with the response in a binary fashion. The current findings extend previous assumptions about saliency thresholds for stimulus VARIABILITY DETERMINES INTEGRATION OF CONTEXT 3 integration into the realm of inter-trial variability and underscore the role of stimulus uncertainty in shaping context integration. Possible underlying mechanisms are discussed.